2015
DOI: 10.1210/jc.2015-1589
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Nuclear Medicine Imaging in Ectopic Cushing's Syndrome: A Systematic Review

Abstract: Nuclear medicine improves the sensitivity of conventional radiology when tumor site identification is problematic. OCT offers a good availability/reliability ratio, and FDG-PET was proven useful. 68Gallium-SSTR-PET/CT use was infrequent, despite offering the highest sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
2
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 143 publications
3
135
2
10
Order By: Relevance
“…Neuroendocrine tumors (NETs), mainly bronchial carcinoids (BC) (3-54.8%), are the most frequent causes of ectopic ACTH secretion in more recent series (3,4,5,6,7,8), whereas small-cell lung carcinoma (SCLC) represented the most common tumor associated with ECS in early series (3.3-50%) (9). Other less-frequent causes are thymic carcinoids (TC) (5-42%), pancreatic (p) NETs (7.5-25%), pheochromocytomas (2.5-25%) and medullary thyroid carcinomas (MTC) (2-8%) (3,4,5,6,7,8). Unknown primary tumors account for .5% of all causes of ectopic ACTH production (3).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroendocrine tumors (NETs), mainly bronchial carcinoids (BC) (3-54.8%), are the most frequent causes of ectopic ACTH secretion in more recent series (3,4,5,6,7,8), whereas small-cell lung carcinoma (SCLC) represented the most common tumor associated with ECS in early series (3.3-50%) (9). Other less-frequent causes are thymic carcinoids (TC) (5-42%), pancreatic (p) NETs (7.5-25%), pheochromocytomas (2.5-25%) and medullary thyroid carcinomas (MTC) (2-8%) (3,4,5,6,7,8). Unknown primary tumors account for .5% of all causes of ectopic ACTH production (3).…”
Section: Introductionmentioning
confidence: 99%
“…As a relatively aggressive tumour, several case reports have demonstrated 18 FDG uptake in thymic NENs, an uncommon finding in most other NENs [47][48][49] . In the latest study which reviewed the reports of patients with thymic carcinoids associated with EAS, the sensitivity of conventional SRS, 18 FDG-PET, and 68 Ga-DOTATOC PET/CT in thymic carcinoids was 12/14, 5/8, and 2/4, respectively, with positivity on CT scanning in 85% [50] . Both conventional SRS and 68 Ga-DOTATOC PET/CT are helpful in surveillance of thymic NENs [51, 52] , but 68 Ga-DOTATOC PET/CT might be the best imaging modality to identify bone metastases in positive patients [53] .…”
Section: Nuclear Medicinementioning
confidence: 99%
“…Many of these tumours may be small and be elusive to imaging modalities, rendering localisation studies a diagnostic challenge. Recent studies have shown a superiority of somatostatin analogue-based PET imaging over CT and MRI scans for localisation studies of these NETs 1 71 72. For example, scintigraphy with 68 Gallium-SSTR-PET/CT was reported to have 100% sensitivity in detecting NET with ACTH or CRH production in a recent study 72.…”
Section: Investigations For Localisationmentioning
confidence: 99%